2019
DOI: 10.1371/journal.pone.0224552
|View full text |Cite
|
Sign up to set email alerts
|

Genetic codes optimized as a traveling salesman problem

Abstract: The Standard Genetic Code (SGC) is robust to mutational errors such that frequently occurring mutations minimally alter the physio-chemistry of amino acids. The apparent correlation between the evolutionary distances among codons and the physio-chemical distances among their cognate amino acids suggests an early co-diversification between the codons and amino acids. Here we formulated the co-minimization of evolutionary distances between codons and physio-chemical distances between amino acids as a Traveling S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 65 publications
0
11
0
1
Order By: Relevance
“…Since error minimization has adaptive value, a prevalent and intuitive view is that this property arose through natural selection 5,6,62 . However, an alternative view is that this trait emerged as a by-product during the initial expansion of the genetic code 36,37,39 . For example, it has been suggested that duplication of aminoacyl-tRNA synthetases would lead to emergence of a conservative pairing, as the tRNA and amino acid would be similar to the ancestral versions 63 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since error minimization has adaptive value, a prevalent and intuitive view is that this property arose through natural selection 5,6,62 . However, an alternative view is that this trait emerged as a by-product during the initial expansion of the genetic code 36,37,39 . For example, it has been suggested that duplication of aminoacyl-tRNA synthetases would lead to emergence of a conservative pairing, as the tRNA and amino acid would be similar to the ancestral versions 63 .…”
Section: Discussionmentioning
confidence: 99%
“…This 'error minimization' confers a clear selective advantage as it reduces the deleterious impact of mutations on the resultant protein 32,33 . However, the standard genetic code does not appear to be particularly optimal with respect to error minimization [34][35][36][37] . This raises a fundamental open question about the origin of error minimization, namely, whether error minimization of the standard genetic code is the product of natural selection, or a serendipitous by-product of the evolution of protein translation 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The objective is to analyze all travel points with the lowest distance. These data will affect the travel e ciency in terms of duration and fuel consumption and route management system (Pintea et al 2017;Attie et al 2019) TSP is a model of the travel to N Cities or N Places which this travel will travel from any one of N Cities by that route. Through all cities in N and return to the starting city to walk like a walking loop (Hougardy & Wilde 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The randomness of the standard genetic code [26] as related to the power law (or Zipf's law) was investigated recently [27]. It should be pointed out that the origin of the triplet code is being investigated from several different perspectives of optimization [28] [29]. The previous study, therefore, may be seen as belonging to this larger class of studies.…”
Section: The Genetic Codementioning
confidence: 99%